PERSEPSI PEGAWAI KANTOR TENTANG PENERAPAN WORK FROM HOME (WFH) PADA MASA PANDEMI COVID 19 DI DESA SUNGAI ASAM KECAMATAN SUNGAI RAYA - Megawati, Megawati; Prancisca, Stella; Al Hidayah, Riama (Universitas Tanjungpura, 2023)
This study aims to define the perceptions of office employees regarding the implementation of work-from-home (WFH) during the Covid 19 pandemic in Sungai Asam village, Sungai Raya sub-district. The sub-problems in this study are the knowledge of office employees regarding the implementation of work from home, what are the evaluations of office employees regarding the implementation of work from home, and what are the actions of office employees regarding implementing work from home during a pandemic in Sungai Asam village, Sungai Raya sub-district. The research method used is a descriptive method with a qualitative research form. Data collection techniques used observation. interviews, and documentation.The analysis in this study was presented in a qualitative descriptive manner using 6 informants, namely village officials and school teachers in Sungai Asam village, Sungai Raya sub-district. The results of this study explain the perceptions of office employees regarding the implementation of WFH during the covid 19 pandemic. The conclusion is that knowledge requires employees to be independent and committed to work such as being closer to technology systems, where the implementation of work from home is carried out in different places or spaces thus prioritizing technological tools to communicate in doing work. The assessment of office staff is quite flexible, some respond positively and some consider that the implementation of WFH provides obstacles for office employees. The actions of office employees are by innovating and utilizing various applications, such as Google Meet, Google Classroom, and WhatsApp, using laptops and cell phones.